Evaluacion de semillas F1 Y F2 sobre algunas caracteristicas agronomica y el rendimiento del cultivo de pimiento (Capsicum annuum) con y sin tutorea en la zona de Quevedo. - Suarez Lalangui, Julia Alexandra (2010)
This research work was carried out at the Finca "La Maria" of the State Technical University Quevedo, located at Km 7 via Quevedo - El Empalme, located at the geographic coordinates 79 º 29 'west longitude and 01 º 06' south latitude, at an altitude of 120 meters. The general objective was: To evaluate the agronomic performance and yield of hybrid pepper (Capsicum annuum) from F1 and F2 seeds with and without specific tutoring as: To evaluate the agronomic characteristics of the hybrid under study in the type of seed planting; establish the response of pepper hybrids to the work of tutoring, determine the advantages and disadvantages of planting seeds F1 and F2. Perform economic analysis of treatments depending on the level of performance and costs. Was used Randomized Complete Block Design with factorial arrangement of 2x2x2 with three replicates and the useful plot formed by the four central rows giving an area of 12m². All variables were subjected to analysis of variance, the Duncan test DMS and 95%. The number of days to flowering hybrids Quetzal Salvador and showed no statistically significant differences, indicating that both hybrids have the same genetic characteristics in this variable and observed a difference of 1.3 days between generations F1 and F2, where F1 is that of begin earlier, this same behavior was observed in the number of days to fruition, while the variables diameter, length, weight and performance of the F1 generation showed the highest rates, exceeding statistically the response of the F2 generation. In the interaction quetzal hybrid generation and tutoring the highest yield was obtained in the F1 generation hybrid Quetzal tutoring with and without tutoring and 28578.37Kg/ha 29734.27. respectively to the remaining statistically differing treatments showed averages between 20852.57 and 26016.63 kg / ha., being the lowest value the F2 generation hybrid Salvador without tutoring